2004
DOI: 10.1021/ct0499276
|View full text |Cite
|
Sign up to set email alerts
|

An Aromaticity Scale Based on the Topological Analysis of the Electron Localization Function Including σ and π Contributions

Abstract: In this work, the average bifurcation value of the electron localization function (ELF) of both σ (ELFσ) and π (ELFπ) contributions was used to construct an aromaticity scale for chemical compounds. We have validated the scale with a series of well-known molecules and then used it to evaluate global aromaticity on aluminum based clusters, which present σ aromaticity and π antiaromaticity. The proposed scaled predicts an overall antiaromatic character for the Al4(4)(-) moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 37 publications
6
126
0
Order By: Relevance
“…Chesnut and Bartolotti, and Santos et al [12,[19][20][21][22] The ELF is defined to have values between zero and one, and in regions where electrons are alone or form pairs of opposite spins, the Pauli principle has little influence on their behavior, and such regions have a low value of excess kinetic energy and a maximum in the ELF. [17,23] Conversely, ELF is small in the regions where Pauli repulsion is large, such as between electron pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Chesnut and Bartolotti, and Santos et al [12,[19][20][21][22] The ELF is defined to have values between zero and one, and in regions where electrons are alone or form pairs of opposite spins, the Pauli principle has little influence on their behavior, and such regions have a low value of excess kinetic energy and a maximum in the ELF. [17,23] Conversely, ELF is small in the regions where Pauli repulsion is large, such as between electron pairs.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the previous studies have focused on the S type structure. [24][25][26][27][28][29][30][31][32][33][34][35][36] However, it is found that both L and S types are stable with no imaginary frequency (except L2 structure which has one imaginary frequency) and the order of stability is S1 $ S2 > L1 > L2 at the CCSD(T)(full)/aug-cc-pVTZ level of theory. Details of total energy evaluations are in the Supporting Information.…”
Section: Resultsmentioning
confidence: 98%
“…Boldyrev and Wang experimentally observed Al 4 Li 3 À cluster and suggested it to be antiaromatic because a Al 4 4À ring in the Al 4 Li 3 À contains four electrons and has a non-equilateral shape. 24) In subsequent reports, arguments ensued concerning whether the compound is truly ''antiaromatic'' [24][25][26][27][28][29][30] or is actually ''netaromatic''. [31][32][33][34] Schleyer and Chen concluded that the Al 4 Li 3 À cluster is net-aromatic because its aromaticity dominates over antiaromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…Topological analyses of the electron localization function (ELF) [22], and in particular the -contribution, ELF  , can be used to directly link molecular electronic structure properties with (anti)aromaticity. This has been exploited by Santos et al, Malrieu et al, and us [23][24][25][26][27]. The ELF  describes the kinetic energy destabilization at position r due to Pauli repulsion between same-spin -electrons, and it takes values in the range 0 ≤ ELF  (r) ≤ 1.…”
Section: Introductionmentioning
confidence: 99%